The Entrepreneurial Competence, Impact of Business Environment and Supply Chain Strategy on Smes Performance: The Intervening Role of Motivation - Agus Setyo Pranowo; Suryana Suryana; M.S Disman; H Mulyadi (International Journal of Supply Chain Management, 2019)
SMEs playsa vital role in the development of economics in Indonesia. The performance of SMEsis also givenan impact on the economic condition. The main factor in the developing SEMs is the supply chain management. Many SMEs in Bogor Regency that fall are lack of motivation and competencies. Another factor that impacts the performance is supporting from business environment this condition support by previous research [1] in Cimahi City and Bandung City, and concluded that small businesses were still lacking in their competencies. Steers & Porter also support this situation [2] states that work motivation is a business that can lead to behavior that is by the work environment in the organization. So the variables are connected as a factor that impacts direct or indirect to performances. This research aims to prove the SMEs competency and business environment have to impact to performance, with motivation, as intervening. It uses SEM-PLS as a method in testing the hypothesis and quantitative with the explanatorymethod. To collect data, a questionnaire used for 100 SMEs taken as a sample in Bogor Regency. The result of this research is that only SMEs competency and motivation has a direct impact on performances, the business environment needs to be intervened by motivation.